The Effect of Independence, Objectivity and Experience on Audit Quality - Milatina Laksmita Dewi (EAJ (Economic and Accounting Journal), 2025)
Quality audits that have high quality and can be trusted are very important, in practice, the auditor must have a responsibility to build trust in the quality of the audits published. The purpose of this study was to examine the effect of Independence, Objectivity and Experience on audit quality at the Regional Inspectorate Office of Semarang City, Kendal Regency and Batang Regency and the study was conducted using a survey approach by distributing questionnaires to 65 respondents using a quantitative descriptive method. The data analysis tool used in this study uses SPSS22 (Statistical Product Software Solution). The analytical method used is Multiple Regression Analysis. Data analysis was performed by descriptive statistical test, reliability test, normality test, multicollinearity test, heteroscedasticity test, T-test, and F test. The results showed that the Independence variable had a positive and significant effect, the Objectivity variable had a positive and significant effect and Audit Experience had a significant effect on Audit Quality.